Design of parallel cyclones based on stability analysis. Issue 12 (24th June 2016) - Zhang, Chenxi; Wang, Qi; Jia, Zhao; Muhammad, Usman; Qian, Weizhong; Wei, Fei
Abstract : The uniform distribution of gas solids flow across parallel cyclones is required for high efficiency. In this study, we introduced mass flow rate ratio between solids and gas (CT ) to present multi‐phase interaction. And the direct Liapunov method is used to detect the instability of uniformity. Due to the special symmetry in this system, the criterion can be simplified into identifying the concavity (concave or convex) of pressure drop across a single cyclone with respect to CT . Then, based on the stability analysis of uniformity, a novel design principle is provided to prevent non‐uniform distribution at dense phase. The effect of geometrical factor, i.e. dimensionless vortex finder diameter dr, on the stability of uniformity has been further investigated. The phase diagram, illustrating the effects of both operational parameter (CT ) and geometrical parameter (dr ) on stability of uniformity is calculated to give a clue of designing a robust parallel cyclones system. © 2016 American Institute of Chemical Engineers AIChE J, 62: 4251–4258, 2016